2011
DOI: 10.1007/s10750-011-0898-7
|View full text |Cite
|
Sign up to set email alerts
|

Paleolimnological reconstruction of the trophic state in Lake Balaton (Hungary) using Cladocera remains

Abstract: The sediment of Lake Balaton (Hungary) provides important information about the lake's history, particularly with regard to eutrophication. In this study, we used fossil pigment analysis and subfossil Cladocera remains preserved in a dated sediment core to identify trophic stages from *250 BC to present. Dates of the most recent eutrophic events are in good agreement with previously published data. In general, the abundance and diversity of the Cladocera community increased with eutrophication and decreased wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 52 publications
(52 reference statements)
1
21
0
Order By: Relevance
“…Müller, 1785) during the German colonization of Lake Gościąź, and a decrease of this species after the demolition of the settlement. As B. longirostris prefers eutrophic conditions (Korponai et al, 2010a(Korponai et al, , 2011, the authors concluded that the German settlers induced an increase in the lake's eutrophic status, which is in line with results provided by other sediment proxies. Galbarczyk-Gąsiorowska et al (2009) could relate changes in cladoceran communities to decreasing water level in Stare Biele mire in Poland.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Müller, 1785) during the German colonization of Lake Gościąź, and a decrease of this species after the demolition of the settlement. As B. longirostris prefers eutrophic conditions (Korponai et al, 2010a(Korponai et al, , 2011, the authors concluded that the German settlers induced an increase in the lake's eutrophic status, which is in line with results provided by other sediment proxies. Galbarczyk-Gąsiorowska et al (2009) could relate changes in cladoceran communities to decreasing water level in Stare Biele mire in Poland.…”
Section: Introductionsupporting
confidence: 82%
“…2). Since mero-and euplanktonic algae exhibit higher production in lentic or slow running waters (Istvánovics and Honti, 2011), and high organic material and pigment contents are found in sediments of highly productive lakes (Korponai et al, 2010a(Korponai et al, , 2011, the increased LOI and SPDU content has been interpreted as a marker for to the development of lentic conditions in the oxbow since 1950. Size distribution of sediment sand (Csépes et al, 2002;Schweitzer et al, 2002), and loading depends on the intensity of flush.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, changes in the pigment composition and stratigraphy reflect variations in the phytoplankton structure and abundance (Leavitt and Hodgson, 2001), which in turn reflects changes in light availability, temperature, nutrients, lake stratification, food web and some other factors (Wetzel, 2001). Several studies across the world have demonstrated that sedimentary pigments can be used to infer past climate changes in Scandinavia and Central Europe (Lami et al, 2000), Antarctica (Hodgson et al, 2005;Chen et al, 2013), Mongolia (Nara et al, 2005), Chile (von Gunten et al, 2009a) and Nepal (Lami et al, 2010) or to document changes in the trophic levels of lakes in Florida (Waters et al, 2005), Chile (von Gunten et al, 2009b), Sweden (Reuss et al, 2010), Hungary (Korponai et al, 2011) and Estonia (Leeben et al, 2013) among others.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Kattel & Sirocko (2011) examined the role of cladocera for reconstruction of the environmental, cultural and archaelogical development in the Eifel maar lakes region (West Germany) during the Late Glacial and Holocene periods; and Korponai et al (2011a) analysed subfossil cladocera assemblages from Late Glacial/Preboreal sediments of Lake Brazi (a South Carpathian mountain lake) to trace the community response to rapid climatic warming that occurred during this period. Korponai et al (2011b), then again, provided a Cladocera-based reconstruction of trophic states in Lake Balaton (Hungary) over the last several thousand years; and López-Blanco et al (2011) presents some interesting data on Cladocera species shifts resulting from hydrological alterations caused by a canal in Lake El Tobar, Spain.…”
Section: Special Issue Contentmentioning
confidence: 99%